(untitled) - Kenrick, Douglas M. (Houndmills, Basingstoke, Hampshire, 1988)
Contents: For centuries Japan, although a totalitarian dictatorship, was ruled by figureheads who signed laws formulated 'behind the screen'. Hierarchy still defines everyone's status. The man at the top has power but jeopardizes his position if he ignores consensus opinions. Nowadays fashionable twentieth-century clothing cloaks a contradictory blend of intense competition with a tradition of harmony dependent on close human-relations and complex communal restraint. The Japanese organise themselves in cliques (not groups) which raise barriers against outsiders. Companies are controlled from within; shareholders are outsiders. Women are more than equal in their homes; less than equal at work. After living and managing his own business in Japan for forty years, the author explored widely before coining the term 'competitive communism' to describe Japan's economic and social system.
Keywords: Japan,Nhật bản; Social conditions,Điều kiện xã hội; 1945-,1945-